ANALYSIS OF THE ROLE OF THE LOCAL GOVERNMENT IN REDUCING POVERTY RATE IN COVID 19 PANDEMIC PERIOD IN SERANG BANTEN CITY - Ombi Romli (International Journal of Economy, Education and Entrepreneurship, 2021)
Poverty is a problem that often arises and becomes a priority in work programs, both for long-established cities and new-born cities, which are the problem of poverty, the numbers of which are increasing, especially during the pandemic like now, which is increasingly out of control, with the emergence of various kinds of waves of layoffs both in absolute and non-real sectors that will cause new social problems, ranging from poverty, social inequality to food shortages, if this continues and cannot find the right solution, and the role of the government is not optimal in carrying out duties and functions. The poverty rate growth will be increasingly out of control. The role of local government as a driving force for regional economic growth is a solution to strengthen central government policies because the central government does not have the power and efforts without the participation and support of local governments. Definition of Regional / Regency Government, The formation of regional government in accordance with the mandate of Article 18 of the 1945 Constitution is the basis of various laws and other statutory regulations that govern regional government. Meanwhile, according to Cahyat, poverty is a situation where a person or household experiences difficulties in fulfilling basic needs, while the supporting environment does not provide opportunities to improve sustainable welfare or escape vulnerability. The research method is a scientific way of obtaining data for specific purposes and uses. The method used in this study is a formative evaluation method, namely seeing and reviewing the implementation and local government programs, seeking feedback to improve the implementation of the intended program in order to reduce the rate of increasing poverty due to the COVID-19 pandemic, the local government of the city of Serang has made every effort to make breakthroughs. Breakthroughs in reducing the rate of increasing poverty due to the COVID-19 pandemic, among others, by opening many new local tourist objects while still implementing health protocols, because all parties want the corona outbreak to be overcome and economic turnover to run, because the tourism sector has the most impact as a result In this pandemic, almost 70% of the industries related to the tourism sector are not able to operate or have gone out of business so that the government must be more optimal in protecting business actors, especially those related to local tourism businesses